Physiological Profiling of Rhizosphere Microbial Communities in Sweet Potatoes - Agustina Monalisa Tangapo; Susan Mambu; Roni Koneri; Marsia Tiara Pasassa; Jesslyn Rumengan (UNIVERSITAS PGRI MADIUN, 2026)
This study investigated the temporal dynamics of sweet potato rhizosphere microbial communities across different growth phases to understand their functional metabolic shifts, which is critical for optimizing sustainable soil management. Rhizosphere soil samples were collected monthly (1 to 5 months) during the crop growth period. Community-Level Physiological Profiling (CLPP) was conducted using the Biolog EcoPlate approach combined with quantitative spectrophotometry analysis, with data evaluated through Average Well Color Development (AWCD), Shannon diversity (H’), and Evenness (E) indices. The results revealed a distict shift in microbial metabolic activity, which peaked at 2 months and gradually declined toward the harvesting phase at 5 months. Ecologically, the substrate utilization pattens shifted dynamically over time: early-stage microbial communities (1-2 months) predominantly utilized carbohydrates and polymers, reflecting the high energy demand and typical root exudates of young plants. Conversely, late-stage communities (3-5 months) transitioned toward amines and polymers, indicating an adaptation to more complex organic matter as the plant matured. This study demonstrates that sweet potato growth stages strongly drive rhizosphere microbial functional diversity. These insights offer an agricultural blueprint for the precise timing of biofertilizer applications aligned with the plant's natural metabolic windows.